Potensi Daun Binahong (Anredera Cordifolia (Tenore) Steenis) dalam Menghambat Pertumbuhan Bakteri Escherichia Coli secara In Vitro - DARSANA, I GEDE OKA; BESUNG, I NENGAH KERTA; MAHATMI, HAPSARI (Faculty of Veterinary Medicine, Udayana University, 2012)
This study examined the response of Escherichia coli codes ATCC (American Type Culture Collection) 25922 obtained from the Laboratorium Daerah of binahong juice leaf with determination test the ability of the inhibition of growth of Escherichia coli by standard Kirby-Bauer disc using five treatments namely binahong juice leaf (0 %, 25%, 50%, 75% and 100%) and negative controls physiological NaCl 0.9% and a positive control with oxytetracycline with repetition as much as four times. Reaction of Escherichia coli growth inhibition by leaf juice and antibiotics binahong shown by the formation of a subsequent inhibition area was measured as the diameter of the circle of the inhibition. Data were obtained, will be tested with Variety Analysis (Test F), followed by Duncan's test of data processing can then proceed to determine the regression analysis. And all the data processed using SPSS. The results of this study indicate that the juice of binahong leaf (Anredera cordifolia (Tenore) steenis) at a concentration of 0% indicates the average resistivity of (0.000 mm); concentration of 25% (7.225 mm); concentration of 50% (8.325 mm) concentration of 75% (10.125 mm) and concentration 100% (12.325 mm). In addition, binahong leaf juice could inhibit the growth of Escherichia coli ATCC 25922, and binahong juice leaf statistically significant (P< 0.01) against the bacteria Escherichia coli and there were highly significant differences (P< 0.01) at each concentration diameter. As well, the increased concentration of binahong leaf juice (Anredera cordifolia (Tenore) steenis) increased the inhibition on the growth of Escherichia coli in vitro.